Lesions of the primate rhinal cortex cause deficits in flavour-visual associative memory. - Parker, A; Gaffan, D (1998)
Three Cynomolgus monkeys (Macaca fascicularis) learned a flavour-visual conditional discrimination problem, in which one of two possible food items was presented at the beginning of each trial, and acted as an instruction cue to signal which of two visually distinct stimulus objects the animal must displace on that trial in order to obtain a further food reward. The task was learned first in light then in dark conditions. Following rhinal cortex ablation the animals were unable to use the flavour properties of the food items to guide visual choices, performing at close to chance levels. Postoperative performance on a food preference test showed that their problem in associating a flavour cue with a visual object in the conditional learning task also extended to aberrant choice of foods based on their visual appearance.